TOURISM INDUSTRY SERVICES AT PT. IRAMASUKA TOURS AND TRAVEL - Akmal Munadi; Riny Jefri; Andi Hajar (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2023)
This research is a qualitative descriptive study that aims to determine the services or services of the tourism industry applied by PT. Iramasuka tours and travels. The existence of customer service is very much needed in corporate organizations, so that it can function as a modern management function which has an inherent function in company management, namely how to play a role in conducting mutual communication for the purpose of creating mutual understanding, mutual respect, mutual trust, creating goodwill, customer satisfaction, decision of the best and so on in order to achieve a positive image for a company. The research have a purpose that to identify and exploring the types of tourism industry services that are applied and the importance of customer service in the world of work at PT. Iramasuka Tours and Travels. This study uses a qualitative approach the data is processed through three qualitative data analysis namely reduction of the data, made the presentation of the data and made the good conclusion.